Body cell mass measured by bioimpedance spectroscopy as a nutritional marker. - Aleksandra Rymarz; Katarzyna Szamotulska; Jerzy Smoszna; Stanisław Niemczyk (The Korean Society of Nephrology, 2012)
Body Cell Mass (BCM) is a sum of all metabolically active cells of the body. Aim of the study was to compare BCM with other nutritional and inflammatory markers in patients with chronic kidney disease (CKD) stage 4-5 (NKF) without dialysis treatment and in hemodialysis patients(HD). We included 45 adult patients with CKD and eGFR<30 ml/min not treated with dialysis (26 male, age: 59,7±16,8) and 39 adults treated with HD three times a week, for more than three months (26 male, 5 diabetics, age: 59,8 ±16). Body composition was measured using multifrequency biopimpedance spectroscopy: Body Composition Monitor - FMC. We used BCM index (BCMI) defined as BCM divided by height to the power of 2. To measure hand grip strength (HGS) we used dynamometr Jamar. In statistics analysis we used Pearson correlations (SPSS v18). Predialysis group: BCMI: 7,1 ±1,6 kg/m², Lean Tissue Index (LTI): 12,9 ±2,4 kg/m², Fat Tissue Index (FTI): 14,7 ±5,4 kg/m², BMI: 28,2 ±5 kg/m², serum creatinine level (SCr): 3,9 ±2,1 mg/dl, eGFR: 18,3 ±7,0034 ml/min/1,73 m², albumin (SA): 3,9 ±0,3 g/dl, prealbumin (PA): 32,8 ±8,8 mg/dl, CRP: 0,5 ±0,3 mg/dl. A positive correlation was found with BCMI and HGS (r = 0,55; p=0,001), PA (r = 0,41; p=0,004) and SCr (r =0,37; p=0,012). A negative correlation was found between BCMI and age (r = -0,48; p=0,006), CRP (r = -0,33; p=0,028). We do not observed correlation with BMI and SA. HD group: BCMI: 6,4±1,7 kg/m², LTI: 12,1±2,3 kg/m², FTI: 12 ±6 kg/m², BMI: 24,8 ±4,8, SCr: 8,9 ±2,6 mg/dl, TP: 6,7 ±0,6 g/dl, SA: 3,9 ±0,47 g/dl, PA 33,8 ±11,4 g/dl, CRP: 1,1 ±1,4 mg/dl. A positive, significant correlation was found between BCMI and HGS (r = 0,47; p=0,003). A negative correlation was found with BCMI and age (r = -0,55; p=0,0005) and with CRP (r = -0,31), but not statistically significant. We do not observed correlation between BCMI and BMI, SCr, TP, SA, PA, hemodialysis vintage, Kt/V. Assessment of body compartments is important tool in estimation nutritional status in patients with stage IV-V CKD and hemodialysis patients. Analysis of body composition in association with other markers worth to be studied, especially in larger groups of patients.